A study of the increased temperature influence on the electrochromic and electrochemical characteristics of Ni(OH)2-PVA composite films - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2020)
Electrochromic devices, as an element of “smart” windows, can be exposed to extreme temperatures due to their purpose and location. Exposure to high temperatures can change the characteristics of electrochromic devices and lead to malfunction. The present study is intended to fill in the gaps related to the stability of electrochemical and electrochromic parameters of one of the known materials – nickel hydroxide (II). The present study highlights changes in some physico-chemical characteristics that occur during prolonged exposure to high temperature in different media. Ni(OH)2-polyvinyl alcohol, prepared using the cathodic template method, was aged at 80 °С under the air atmosphere and in the working electrolyte solution – 0.1 М KOH for 8 hours. The temperature was chosen based on the maximum registered temperature on Earth, possible film heat up and possible rapid degradation of electrochromic films. As a result, it was found that degradation does occur in a basic solution, while on air some improvement was observed instead. The authors propose the mechanism that explains experimental results, which lies in “ageing” of active material Ni(OH)2. The latter occurs in the active mass of alkaline batteries. Possible methods for preventing degradation are also proposed, which can be realized with the use of thickened electrolytes or special films that are deposited onto the electrochrome